2020
DOI: 10.31254/jmr.2020.6502
|View full text |Cite
|
Sign up to set email alerts
|

Understanding SARS-CoV-2 infection in males

Abstract: The worldwide spread of the emerging respiratory disease produced by SARS-CoV-2 has become a matter of great concern to public health. The expression of the viral receptor ACE2 in the male reproductive tract arises hypothesis about a possible targeting to testicular tissue during the infection and further implications to male fertility. However, current data of whether the virus is present or not in the seminal fluid is contrasting. Objectives: The propose of this opinion article was to describe the impact SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…To date, it is understood that although the general infection rate is similar in men and women (50%), deaths in the male population are higher. 1 It has even been reported that the prostate expresses the virus receptor, which could negatively affect the seminal quality and could have a severe effect on human reproduction. 2 3 Therefore, this commentarýs objective was to analyze the scientific data published to date on the presence of the virus in semen.…”
Section: Figmentioning
confidence: 99%
“…To date, it is understood that although the general infection rate is similar in men and women (50%), deaths in the male population are higher. 1 It has even been reported that the prostate expresses the virus receptor, which could negatively affect the seminal quality and could have a severe effect on human reproduction. 2 3 Therefore, this commentarýs objective was to analyze the scientific data published to date on the presence of the virus in semen.…”
Section: Figmentioning
confidence: 99%